ANALISIS PENGARUH INFRASTRUKTUR, INVESTASI DAN TENAGA KERJA TERHADAP PERTUMBUHAN EKONOMI DI PULAU JAWA - Alfarabi Ihsan Hazimi (2022)
The purpose of this study is to determine whether infrastructure, investment, and labor will have an impact on Java's economic growth, which is seen using data from six provinces in Java. High economic growth is an important foundation for the continuity of economic development, an indicator of the success of a country's development, and can later be used to increase the prosperity of the people. This study uses data from six provinces on the island of Java (DKI Jakarta, West Java, Central Java, East Java, DI Yogyakarta, and Banten) from 2010 to 2019. The data in this study uses panel data analysis using the Common Effects (CEM) method. The data is processed with Eviews 10 software. The results of this study indicate that the variables of infrastructure, investment, and labor have a positive and significant impact on economic growth.